Soil management and basal leaf removal effects on microclimate, yield, fruit composition on the portuguese vine variety Fernão Pires in Bairrada region - Cruz, Amândio (2007)
The study, throughout two years (2004 and 2005), of different systems of soil management, as well as different basal leaf removal modalities, effects on the white variety ‘Fernão Pires’, took place in a vineyard pertaining to Sogrape Vinhos, SA, located in the Bairrada Demarcated Region (littoral/centre of Portugal). Two techniques of soil management between rows were applied: the permanent natural grass cover and tillage, both with application of herbicide on the row. In 2004, basal leaf removal was carried through at veraison on the two sides of canopy or only on the East side. In 2005, other basal leaf removal modalities were introduced, at pea size or at veraison, applied only on one or two faces of canopy. In the two years of the experiment, the climate during the vegetative cycle was dry, especially in 2005. In consequence the predawn leaf water potential reached very low values along ripening and differences between grass covered and tilled treatments have not been registered. Higher net photosynthetic rates were obtained in tilled treatment, probably due to greater magnesium content in the leaves. Grass cover conduced to a less dense canopy, especially in 2005, by a reduction of the leaf layer number (LLN), higher penetration of photosynthetically active radiation (PAR) at cluster zone and in 2005, provoked a drastic increase on the proportion of sunburned leaves and scalded clusters. On the other hand, basal leaf removal also modified the canopy structure, reducing its density, particularly in 2004. In this year, high bunch rot (Botrytis cinerea L.) incidence occurred and the reduction of canopy density had an important role on it’s the decrease. In 2004, yield components hadn’t been significantly affected by any of the factors in study. However in 2005, although basal leaf removal haven’t influenced yield, grass cover strongly reduced it (about 50%). Vigour reduction was verified in both years only by grass cover. Small differences between treatments were found in what concerns to must composition. At harvest in 2005, soil management techniques didn’t influenced nutritional cluster composition